Approaches to Nutrient Use Efficiency of Different Strawberry Genotypes - Agüero, Juan José; Kirschbaum, Daniel Santiago (2018)
In annual strawberry (Fragaria x ananassa Duch.) production systems in Argentina, fertilizers are frequently applied without considering soil fertility, cultivar particularities, and nutrient use efficiency (NuUE). The objective of this study was to investigate the NuUE of different strawberry cultivars. In 2006, 2007, and 2008, field plots of ‘Camarosa’, ‘Camino Real’, ‘Candonga’, and ‘Ventana’ were fertilized at different nutrient rates. Control treatment (“C”) was 120 N, 70 P2O5, 220 K2O, 40 CaO, and 20 MgO (kg/ha). In 2006, treatments were “C” and “1.5C”, in 2007, “C”, “1.33C” and “1.66C”, and in 2008, “C”, “1.5C” and “2C”. Productivity from the applied-nutrients was inversely proportional to the applied-nutrient rate, and it was higher in high-yielding cultivars (‘Camarosa’ and ‘Ventana’). Optimal N dose (in kg/ha) was 183, 196, 165, and 150, for ‘Camarosa’, ‘Ventana’, ‘Camino Real’, and ‘Candonga, respectively. Apparently, NuUE is cultivar related, and might become a useful tool for adjusting fertilization programs and characterizing new cultivars in breeding programs.